2009
DOI: 10.1007/s12031-009-9238-z
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Involvement in Alzheimer’s Disease. A Link with NGF Maturation and Degradation

Abstract: Basal forebrain cholinergic neurons are highly dependent on nerve growth factor (NGF) supply for the maintenance of their cholinergic phenotype as well as their cholinergic synaptic integrity. The precursor form of NGF, proNGF, abounds in the CNS and is highly elevated in Alzheimer's disease. In order to obtain a deeper understanding of the NGF biology in the CNS, we have performed a series of ex vivo and in vivo investigations to elucidate the mechanisms of release, maturation and degradation of this neurotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 19 publications
4
75
0
1
Order By: Relevance
“…Maturation failure or increased degradation of NGF might be responsible for the vulnerability of cholinergic neurons in the medial frontal cortex of patients with AD [18,19,46]. Since cholinergic neurons influence the neurocognitive attentional function of rodents and humans, cholinergic drugs (acetylcholine esterase inhibitors) or NGF gene injection into BCNs have improved attention deficits and cerebral metabolism in early-stage AD [5,7,46,47,48,49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maturation failure or increased degradation of NGF might be responsible for the vulnerability of cholinergic neurons in the medial frontal cortex of patients with AD [18,19,46]. Since cholinergic neurons influence the neurocognitive attentional function of rodents and humans, cholinergic drugs (acetylcholine esterase inhibitors) or NGF gene injection into BCNs have improved attention deficits and cerebral metabolism in early-stage AD [5,7,46,47,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis was advanced that NGF reduction led to vulnerabilities in the cholinergic system including associated enzymes, such as choline-acetyl transferase and acetylcholine esterase [14,15]. Moreover, some previous reports have supported a ‘neurotrophic deficit’ hypothesis, in which a reduction in NGF would cause the deterioration of basal forebrain cholinergic neurons (BCNs) and an NGF/tropomyosin-related kinase A signaling system dysregulation, resulting in the neuropathological changes of AD including amyloid-β accumulation and cognitive impairments [16,17,18,19,20]. While a regional increase in proNGF levels was shown in the frontal, hippocampus and parietal cortex of patients with MCI, early-stage AD and late-stage AD, the mature NGF levels were not reduced in the frontal and hippocampus cortex of postmortem brain tissue in patients with AD [21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, evidence has been provided to support a model in which the formation of an inter-protomer disulfide bond in p75 allows a scissoring (or snail-tong) action upon NGF binding that promotes binding of intracellular adaptor proteins (Simi & Ibanez, 2010;Vilar et al, 2009). As mentioned above (Section 2.2), proneurotrophins may play significant role in AD, due to their ability to stimulate p75 in the absence of positive Trk signals thereby promoting apoptosis and death of neurons or glia (Cuello et al, 2010;Fahnestock et al, 2001;Teng, et al 2010). These effects are thought to be mediated by the same pathways ( Fig.…”
Section: P75 Signalingmentioning
confidence: 90%
“…However, recent studies showed that proNGF, the precursor form of NGF, is really largely exist in central nervous system tissues, and has biological functions exceeding its role as a precursor (17,28,29). ProNGF could induce cell death by binding to p75NTR with high affinity (30)(31)(32).…”
Section: Ngfmentioning
confidence: 99%